2002
DOI: 10.1063/1.1447506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grain size on the residual loss of Mn–Zn ferrites

Abstract: The effect of grain sizes on the electromagnetic properties of Mn–Zn ferrites has been studied up to MHz range. The average grain sizes ranging between 2 and 5 μm were obtained by varying the sintering time from 2 to 12 h. The total power loss at 1 MHz, 25 mT, and 100 °C increased with grain size. The hysteresis loss decreased with increasing grain size, while the eddy current loss and the residual loss increased. The residual loss showed a drastic increase at the grain size around 4 μm, which confirms that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…6 displays P r of MnZn ferrites doped with different NiO contents. P r reduces gradually with increasing NiO, and at 100 • C is higher than that at 25 • C. According to Jeong et al's report [21], P r should be decreased with the decline of average grain size (D). This means that the main part of P r is actually resonance loss.…”
Section: Temperature Characteristic Of Lossesmentioning
confidence: 92%
“…6 displays P r of MnZn ferrites doped with different NiO contents. P r reduces gradually with increasing NiO, and at 100 • C is higher than that at 25 • C. According to Jeong et al's report [21], P r should be decreased with the decline of average grain size (D). This means that the main part of P r is actually resonance loss.…”
Section: Temperature Characteristic Of Lossesmentioning
confidence: 92%
“…As we can see, the average diameter of the grain is about 2.55 mm, which reduces the P r in high frequencies, and also makes the high peak of complex permeability. In Mn-Zn ferrite, it is reported that a transition in the intragranular domain structure from the single domain to the multiple domain state occurs at the grain size 3.870.7 mm [6,14]; it is also found that there is a drastic increase in P r at the grain size around 4 mm [15], suggesting that P r due to the domain wall resonance should be taken into account at the grain size greater than single domain dimensions. This means when the grain size is greater than the single domain dimension, P r due to domain wall relaxation process as well as the rotational resonance process should be taken into account.…”
Section: Article In Pressmentioning
confidence: 95%
“…These results reveal that cores sintered at 1,000°C started to operate when the frequency is above kHz order. It is evident that magnetic induction (low hysteresis loss) is more important than electrical resistance of ferrite cores in kHz order frequency range [25]. Mn-Zn ferrite cores with large size grains work well in kHz frequency range due to their better magnetic induction and low hysteresis losses.…”
Section: Effect Of Sintering Temperature On Gain Responsementioning
confidence: 99%